A Comparison of Postoperative Outcomes Based on Muscle versus Fasciocutaneous Flaps in Scalp Reconstruction: A Systematic Review and Meta-analysis - Stanton, Eloise W.; Pekcan, Asli; Roohani, Idean; Choe, Deborah; Carey, Joseph N.; Daar, David A. (Journal of Reconstructive Microsurgery, 2024)
Background Scalp reconstruction in plastic and reconstructive surgery often necessitates the transfer of soft-tissue flaps to restore form and function. The critical decision lies in choosing between muscle-containing (MC) and fasciocutaneous (FC) flaps for scalp reconstruction, and while both variants have their merits, flap composition remains a subject of ongoing debate. This scientific discussion aims to explore this contentious issue through a comprehensive meta-analysis, shedding light on the rationale behind the choice of these flaps and the potential impact on clinical outcomes.Methods A comprehensive systematic review was conducted following PRISMA-P guidelines, encompassing six prominent databases up to the year 2023. Data were collected from studies assessing outcomes of MC and FC flaps for scalp reconstruction. Quality evaluation was performed using ASPS criteria and the ROBINS-I tool. Statistical analysis included descriptive statistics, meta-analysis, sensitivity analysis, and assessment of bias using STATA software.Results The meta-analysis included 28 nonrandomized studies, totaling 594 flaps (MC: 380, FC: 214). MC flaps were significantly larger than FC flaps. There were no significant differences in flap loss, flap necrosis, or wound dehiscence between the two flap types. However, the incidence of venous congestion was significantly higher in FC flaps. Sensitivity analysis confirmed the robustness of results, and publication bias assessment showed no significant evidence of bias.Conclusion While both MC and FC flaps offer viable options for scalp reconstruction, the choice should be tailored to individual patient characteristics and defect size. FC flaps may provide advantages such as shorter operative times and reduced morbidity, whereas MC flaps could be preferred for addressing larger defects. Future research should focus on prospective studies and strategies to mitigate venous congestion in FC flaps, enhancing their safety and efficacy in scalp reconstruction.
Keywords: flap; scalp reconstruction; muscle; fasciocutaneous; myocutaneous